1997
DOI: 10.1037/0278-6133.16.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Psychological responses to BRCA1 mutation testing: Preliminary findings.

Abstract: The short-term psychological responses of 60 adult women tested for a BRCA1 gene mutation associated with a high risk of breast and ovarian cancer were investigated. Participants were members of a large kindred enrolled in an ongoing prospective study of the psychosocial impact of genetic testing. Initial results from participants who completed both the pretest baseline and the 1-2 week posttest follow-up interviews are reported. Gene mutation carriers manifested significantly higher levels of test-related psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
230
5
11

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 284 publications
(273 citation statements)
references
References 22 publications
27
230
5
11
Order By: Relevance
“…Previous studies on genetic testing for a BRCA1/2 mutation did not find substantial psychological morbidity among women initiating genetic testing or receiving a positive test result (Lerman et al, 1996(Lerman et al, , 1998Croyle et al, 1997;Lodder et al, 1999Lodder et al, , 2001Coyne et al, 2000;Schwartz et al, 2002), which is in agreement with the well-being levels in our study. The DA had no negative impact on a broad range of well-being outcomes, and did not deter women from receiving their test result, while it improved understanding of the treatment options and consequences.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on genetic testing for a BRCA1/2 mutation did not find substantial psychological morbidity among women initiating genetic testing or receiving a positive test result (Lerman et al, 1996(Lerman et al, , 1998Croyle et al, 1997;Lodder et al, 1999Lodder et al, , 2001Coyne et al, 2000;Schwartz et al, 2002), which is in agreement with the well-being levels in our study. The DA had no negative impact on a broad range of well-being outcomes, and did not deter women from receiving their test result, while it improved understanding of the treatment options and consequences.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research focused on individual responses (e.g., Croyle et al, 1997;Lerman et al, 1996) had noted reduced distress among individuals who tested negative, so we had expected more friendly interpersonal responses among the negative dyads. However, the overall pattern of results for negative dyads suggests a relatively neutral, less invested relationship pattern than the other groups.…”
Section: Same-results Dyadsmentioning
confidence: 96%
“…53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…The most robust predictor of future distress is distress at baseline. 32,49,[57][58][59]68,[74][75][76][77] Additional risk factors include prior psychiatric history of depression, 74 history of using psychotropic medications, 75 passive or avoidant coping styles, 51,75,[80][81][82] or inaccurate risk perception, [85][86][87] which put individuals at risk of experiencing distress throughout the process or many years after receiving their results. Other important risk factors for future distress include being the first member of the family to obtain genetic testing, 33 having children, 76 experiencing the death of a relative from hereditary cancer, 34,78 as well as experiencing unresolved loss 5 and complicated grief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation